Re-irradiation for painful bone metastases using stereotactic body radiotherapy. (2nd December 2018) - Ogawa, Hiroaki; Ito, Kei; Shimizuguchi, Takuya; Furuya, Tomohisa; Nihei, Keiji; Karasawa, Katsuyuki
Abstract: Purpose: Stereotactic body radiotherapy (SBRT) is expected to achieve safe and effective re-irradiation for painful bone metastases. This study aimed to clarify the efficacy of re-irradiation using SBRT for painful bone metastases. Methods: Prospective database at our institution for the period between September 2013 and December 2017 were retrospectively reviewed for patients with: (1) painful bone metastases; (2) history of radiotherapy to the metastasis; and (3) SBRT performed as re-irradiation. Pain response, pain failure-free duration, analgesics medications, and adverse events were evaluated. Pain was evaluated using the Numerical Rating Pain Score, and pain response was evaluated based on International Consensus Pain Response Endpoints. Best response during follow-up was noted. Patients with complete or partial response were defined as showing pain response, and patients with pain progression were defined as showing pain failure. Adverse events were evaluated based on the RTOG/EORTC Late Radiation Morbidity Scoring Schema. Results: Sixty-six patients selected from our database showed: median age, 65 years (range, 33–82 years); ECOG performance status, 0–1/2/3/4, 51/10/3/2; lesion histopathology, rectal/lung/renal/thyroid/other cancer, 13/11/9/5/28; median previous irradiated dose, 30 Gy (range, 8–70.4 Gy); median interval from latest irradiation, 21 months (range, 4–192 months); prescribed dose for SBRT, 24 Gy in 2 fractions/30 Gy in 5 fractions/35 Gy in 5 fractions, 51/13/2. Median follow-up after SBRT was 10 months (range, 1–37 months). Fifty-seven patients achieved pain response (86%). The 1-year pain failure-free rate was 55%. Median pain failure-free duration was 13 months (range, 1–24 months). Grade 4 adverse events were observed in six patients (vertebral compression fracture, n = 5; radiation myelopathy, n = 1). No other toxicities of Grade 3 or greater were encountered. Conclusions: Re-irradiation SBRT has potential to achieve good response and long-term pain control for painful bone metastases. Prospective analysis is necessary to confirm the safety and efficacy of SBRT as re-irradiation.